Pelatihan Budidaya Hidroponik dan Optimalisasi Sistem Pemberian Nutrisi pada Kebun Hidroponik dengan Menggunakan Mikrokontroler di Pondok Pesantren Darul Fithrah - Sofyan, Yusuf; Fitriani, Sofy; Nurdin, Muhamad Irfan (Universitas Nusantara PGRI Kediri, 2025)
Darul Fithrah Islamic Boarding School (Ponpes DF) is a tahfiz Al-Qur'an-focused Islamic boarding school with education levels from kindergarten to high school. This Islamic boarding school has various active extracurriculars, one of which is hydroponic extracurriculars. This extracurricular is very useful for improving students' abilities. However, currently, there are still various shortcomings, one of which is related to the capability and application of technology in gardens. In order to fulfill this, training activities are carried out in this community service, and automatic nutrient control technology in hydroponics is applied. The training is aimed at students and hydroponic extracurricular administrators. This training activity focuses on explaining various methods and types of plants that can be cultivated using the hydroponic method, then training on the use of automatic nutrient control in hydroponic gardens. Based on the results of training and the application of automatic nutrient control technology, students and administrators can understand various types of hydroponic cultivation methods and then know how to plant various other types of plants that can be cultivated so that there can be a greater variety of plants that can be planted in the garden. Finally, based on the results of the application and training of automatic nutrient control technology, the students and administrators consider that the application of this technology is beneficial in the process of monitoring and maintaining plant quality.